Low temperature synthesis of chromium carbide (Cr3C2) nanopowders by a novel precursor method. (January 2015) - Zhao, Zhiwei; Zheng, Hongjuan; Liu, Shaojing; Shen, Jianhong; Song, Weiqiang; Chen, Jinshen
Abstract: Chromium carbide (Cr3 C2 ) nanopowders have been synthesized by a novel solution-derived precursor method, and the raw materials are ammonium dichromate ((NH4 )2 Cr2 O7 ) and glucose (C6 H12 O6 ). The products were characterized by X-ray diffractometry (XRD), thermogravimetric and differential scanning calorimetry (TG-DSC), transmission electron microscopy (TEM) and X-ray photoelectron spectroscopy (XPS) techniques. The results show that Cr3 C2 nanopowders with an average crystallite size of 32 nm can be synthesized at 900 °C in 1 h. The powders synthesized by this approach show good dispersion and are mainly composed of spherical or nearly spherical particles with a mean diameter of about 30 nm. The weight loss ratio of the precursor during the reaction is about 55 wt.%, and it reduces rapidly before 400 °C (about 45 wt.%). The surface of the specimen mainly consists of three elements, Cr, C and O. The XPS spectrum of Cr2p consists of two peaks with the binding energies of 575.8 eV and 577.4 eV, which are assigned to the Cr2p3/2 species of Cr3 C2 -x (0 ≤ x ≤ 0.5) and Cr2 O3, respectively. Highlights: A novel precursor method was used to synthesize Cr3 C2 nanopowders. (NH4 )2 Cr2 O7 and C6 H12 O6 were used as raw materials. Single phase Cr3 C2 nanopowders can be synthesized at 900 °C in 1 h. The synthesis temperature is at least 500 °C lower than that of conventional methods. The powders show good dispersion and consist of particles of about 30 nm.